2008
DOI: 10.22452/ajap.vol1no1.2
|View full text |Cite
|
Sign up to set email alerts
|

A Survey On Financial and Management Accounting Practices Among Small and Medium Enterprises in Malaysia

Abstract: In the current business environment, firms are faced with intensifying competition locally and globally, and fast changes in customers and technologies. In this environment it is vital that small and medium enterprises (SMEs) are equipped with appropriate and modern financial and management accounting practices in order for them to survive and remain profitable. One of the factors that determine the performance of a business organization is effective use of financial and management accounting reports. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…They ranked the managerial information as a second source of information needed for internal decision making. These results coincide with the study of Isa et al (2007) which found that financial accounting reports were perceived to contain important information needed for management purposes. The study also shows that business type is an influential variable behind respondents' views of the influence of financial accounting on management accounting information.…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…They ranked the managerial information as a second source of information needed for internal decision making. These results coincide with the study of Isa et al (2007) which found that financial accounting reports were perceived to contain important information needed for management purposes. The study also shows that business type is an influential variable behind respondents' views of the influence of financial accounting on management accounting information.…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 89%
“…In such a business environment, managers need relevant “management accounting” information in order to make value‐adding decisions (Atkinson, 1987; Agbejule, 2005). Consequently, the management accounting system has attracted significant attention since it is the system that supplies appropriate information enabling managers to continually adjust their business activities in response to their corporations' environment (Drury and Tayles, 2005; Isa et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Micro and small entrepreneurs have been acknowledged by the world, because they play a very important part in the development of a country regardless of whether it is a developed or a developing country (see Cassells and Lewis 2011;Isa et al, 2008;Hairuddin et al, 2012;Rasiah, 2002). There is no specific definition for micro and small enterprises (MSEs) because the definition depends on many factors (Kushnir, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been established that the use of appropriate bookkeeping, financial reporting and management accounting, Practices are important to the survival of SMEs (Bowen, 2009;Isa, Saleh & Sapiei, 2007), scarcely will you find sufficient reported research on the subject in the sector, particularly in Ghana where just a handful of studies has been reported in recent times. Studies on SMEs in Ghana have focussed on some aspects of financial management practices like bookkeeping, and to a lesser extent working capital management without comprehensively examining the entire financial management practices of SMEs and how these can affect their growth and profitability.…”
Section: Introductionmentioning
confidence: 99%